#TITLE_ALTERNATIVE# - AKBAR (NIM 12004051), PRATAMA
Along with rapid population growth, human need of ground water also increases. Therefore, research about groundwater exploration in different geological conditions needs to be done. Hydrogeological mapping is a method to determine the distribution of groundwater in an area. Case study for this research is in Gunung Padang area, in Bandung Regency, West Java. Geological and hydrogeological conditions of this area have not been much studied previously. Therefore, geological and hydrogeological conditions of this area are interesting enough to study. Geomorphology Gunung Padang Area are divided into four geomorphologic units. These units are Volcanic Denudational Hills Unit (V14), Lower Volcano Slope Unit (V7), Volcanic Neck Unit (V15), and Intervolcanic Plain Unit (V12). The lithologic units in this area are divided into Breccia I Unit, Andesitic Lava I Unit, and Andesitic Intrusive Unit which formed in the Pliosen epoch, and unconformable overlying these units are Breccia II Unit, Andesitic Lava II Unit, and Tuff Unit which formed in Plistosen epoch. Geological structure in the research area are one major fault (Caringin Fault), two minor faults (Rawabogo and Babakan Cimahi Fault) which cut Breccia I Unit, and one anticline (Mekarwangi Anticline). Caringin Fault is a normal sinistral fault, and has N169.60E/64.70SW strike and dip. Hydrogeological system in the study area is volcanic hydrogeological system which has unconfined aquifer type. Based on observation of permeability on the field, aquifer in the study area consists of weathering and fractures of Breccias I, weathering and fractures of Andesitic Lava I, weathering of Breccias II, weathering of Andesitic Lava II and Tuff Unit. Based on water table data, there are six groundwater flow directions which are to the southwest in Desa Mekarwangi, to the northwest in Desa Wangunsari, to the northeast in Desa Lebakmuncang, and to the east, southeast, and south in Desa Rawabogo. Based on pH and TDS values, groundwater in the research area can be consumed directly.